THE CONTRIBUTION OF METACOGNITIVE AWARENESS AND LEARNING ENVIRONMENT ON ACADEMIC ACHIEVEMENT OF THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT, GANESHA UNIVERSITY OF EDUCATION - ., Putu Seriardana; ., Putu Eka Dambayana S., S.Pd.; ., Prof. Dr. Anak Agung Istri Ngr. Marha (Jurnal Pendidikan Bahasa Inggris undiksha, 2016)
This study was a correlational study with ex-post facto research design, which aimed at investigating (1) the contribution of metacognitive awareness on students’ academic achievement, (2) the contribution of learning environment on students’ academic achievement, (3) the simultaneous contribution of metacognitive awareness and learning environment on academic achievement of the fourth semester students of English Education Department, Ganesha University of Education in academic years 2015/2016. Ex-post facto research design was a research design to investigate the correlation between independent variables and dependent variable by (1) determining the sample, (2) designing and developing the questionnaires, (3) distributing the questionnaires, (4) analyzing the obtained data, and (5) drawing the conclusion. The sample of the study was chosen by using simple random sampling technique, in which there were 145 students. The analysis was conducted based on multiple linear regression test supported by SPSS version 16 program. This study reveals that: (1) there is no contribution of metacognitive awareness on students’ academic achievement; (2) there is no contribution of learning environment on students’ academic achievement; and (3) there is no contribution of metacognitive awareness and learning environment on students’ academic achievement. keyword : metacognitive awareness, academic achievement, learning environment